Investigation into the hovering flight dynamics and control of a flapping wing micro air vehicle - Loh, K. (Cranfield University, 2003)
The hovering flight of a micro air vehicle was investigated. Various flight control concepts, inspired by observation of insect and bird flight, were investigated in some detail. The concepts make use of flap frequency or phase between the flap and pitch attitudes of the wing to control the force magnitude. Tilt of the stroke plane or fuselage was used to vector the force. A flight control system was designed for each concept investigated. The investigation has revealed that the preferred control concept is one in which force vectoring is achieved by the fuselage tilt through a shift in the centre of gravity location while the force magnitude is controlled by the phase between pitch and flap attitudes. This has the advantage of reducing the vehicle weight while at the same time relaxing the demand of extremely high frequency actuators. The equations of motion based on a multi-body representation of a flapping wing micro air vehicle were derived and these form the basis for the SIMULINK flight simulation program used to carry out the above investigation. The aerodynamic model used for the simulation was obtained from force measurements with a flapping mechanism that allows the model wing to oscillate with two degrees of freedom (flap and pitch). During these measurements, the phase angle between the flap and pitch angles of the model wing was varied to determine the effects on the force magnitude and direction.